Validation of the "Charles Handy Organizational Culture Questionnaire" in the Fire Department of Karaj - Javaheri, Leila; Amoei Dizaji, Khadijeh; Shahani Shalamani, Roghayeh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: This study aimed to translate and psychometrically evaluate the "Charles Handy Organizational Culture Questionnaire" in the Fire Department of Karaj.Methodology: The study employed a validation research design, using a sample of 294 employees and personnel of the Karaj Fire Department in 2021, selected through simple random sampling. The original English version of the questionnaire was translated into Persian, and exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were conducted to assess the construct validity. Internal consistency was evaluated using Cronbach’s alpha.Findings: Exploratory factor analysis revealed two main components, "Organizational Preferences" and "Personal Preferences," explaining 65% of the total variance. The Cronbach’s alpha coefficients were 0.81 for organizational preferences and 0.88 for personal preferences, indicating acceptable internal consistency. Confirmatory factor analysis supported the two-factor structure of the questionnaire, with all fit indices showing a good model fit.Conclusion: The Persian version of the "Charles Handy Organizational Culture Questionnaire" was found to have acceptable validity and reliability, making it a suitable tool for assessing organizational culture in Iranian organizations, particularly in the fire department context.